2008
DOI: 10.1007/s10393-008-0180-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological Diversity, Dietary Diversity, and Eye Health in Developing Country Populations: Establishing the Evidence-base

Abstract: Human and ecosystem health converge around biological diversity issues. Cultivated and wild plants as food and medicine make essential contributions to human health, which in turn provides rationales for conservation. While wild and cultivated plant diversity reasonably facilitates dietary diversity and positive health outcomes, the challenges of demonstrating this relationship limit its impact in concept, policy, and practice. We present a rationale for testing the dietary contribution of biological diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 88 publications
(105 reference statements)
0
16
0
Order By: Relevance
“…Although many traditional systems in Latin America have proved their durability in the long term 19 , researchers face serious methodological challenges inherent in measuring the relationship between biodiversity and food security within a common framework 222224 . In emphasizing the collective right of food producers and consumers to decide the characteristics of their food system at local, regional and national levels, food sovereignty contains a crucial ambiguity—that is, the question of how to resolve possible contradictions within these different geographies, from the nation-state to the individual 225 .…”
Section: Resultsmentioning
confidence: 99%
“…Although many traditional systems in Latin America have proved their durability in the long term 19 , researchers face serious methodological challenges inherent in measuring the relationship between biodiversity and food security within a common framework 222224 . In emphasizing the collective right of food producers and consumers to decide the characteristics of their food system at local, regional and national levels, food sovereignty contains a crucial ambiguity—that is, the question of how to resolve possible contradictions within these different geographies, from the nation-state to the individual 225 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several traditional production practices have been documented to result in high agrobiological diversity (Altieri, 2004;Clawson, 1985), which can facilitate dietary diversity (Bélanger and Johns, 2008;Penafiel et al, 2011). It is important to note, however, that traditional food production systems need sufficient food safety checks to monitor the risk of exposure to toxins, either organic (Benkerroum, 2013;Wild and Gong, 2010) or inorganic (Isildak et al, 2004;Larsen, 2006;Muhammad et al, 2011).…”
Section: Availabilitymentioning
confidence: 99%
“…Even though the nature of the evidence is still circumstantial, many authors find that there is a reasonable and compelling case to argue that access to and use of biological diversity from both forests and farm land leads to a more varied diet [4,41,42], which in turn improves health outcomes [43,44]. A study by Powell et al [18] in the East Usambara Mountains (Tanzania), showed that 48% of the food species consumed could be obtained in forest ecosystems (Figure 2), and children who had used forest foods had diets with higher diversity and nutrient density, and consumed a larger number of animal source food items.…”
Section: Nutritional Quality Of Forest Foodsmentioning
confidence: 99%